2020
DOI: 10.1038/s41396-020-0587-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycelial network-mediated rhizobial dispersal enhances legume nodulation

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 67 publications
0
55
0
2
Order By: Relevance
“…This trend of enrichment of Actinomycetales associated with roots has also been observed under drought conditions in the rhizosphere of rice, another wet-adapted plant species (Santos-Medellín et al, 2017). While there are many unicellular taxa within Actinomycetales, members of the group are largely recognized for their ability to form branching hyphae during parts of their life cycles (Barka et al, 2016;Goodfellow & Williams, 1983 bacteria have been previously demonstrated to require either saturated conditions or fungal hyphae ("fungal highways") in order to move towards resources (e.g., roots) within the soil profile (Quelas et al, 2016;Wolf et al, 2013;Zhang et al, 2020). In conjunction with the decline in Bradyrhizobium sp., we saw a relative increase in the second most abundant root OTU (OTU-2 Streptomyces sp.…”
Section: Bacterial Morphology As a Mediator Of Bacteria Community Rmentioning
confidence: 99%
See 3 more Smart Citations
“…This trend of enrichment of Actinomycetales associated with roots has also been observed under drought conditions in the rhizosphere of rice, another wet-adapted plant species (Santos-Medellín et al, 2017). While there are many unicellular taxa within Actinomycetales, members of the group are largely recognized for their ability to form branching hyphae during parts of their life cycles (Barka et al, 2016;Goodfellow & Williams, 1983 bacteria have been previously demonstrated to require either saturated conditions or fungal hyphae ("fungal highways") in order to move towards resources (e.g., roots) within the soil profile (Quelas et al, 2016;Wolf et al, 2013;Zhang et al, 2020). In conjunction with the decline in Bradyrhizobium sp., we saw a relative increase in the second most abundant root OTU (OTU-2 Streptomyces sp.…”
Section: Bacterial Morphology As a Mediator Of Bacteria Community Rmentioning
confidence: 99%
“…Just as plants with different growth morphology such as trees, shrubs, or grasses might dominate different parts of environmental gradients, the broad‐scale growth morphology of microorganisms (e.g., unicellular or filamentous) may also play a role in these distribution of these taxa (Daws et al., 2020). For instance, unicellular, flagellate bacterial taxa require saturated soil conditions in order to swim towards and colonize pools of resources such as roots (Quelas et al., 2016; Zhang et al., 2020). Conversely, bacteria that grow filamentously are less likely to depend on soil saturation for motility and subsequent root colonization as they are able to grow towards resources (Wolf et al., 2013; Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, fungal hyphae are capable of serving as vectors for the dispersion of bacteria in the rhizosphere, which is known as a “fungal highway” ( Kohlmeier et al, 2005 ; Warmink et al, 2011 ; Figure 1B ). In a recent study, Zhang et al (2020) showed that rhizobia use mycelia of Phomopsis liquidambaris as dispersal networks to migrate into legume rhizospheres and to trigger nodulation. Extraradical mycelium formed by the mycorrhiza fungus Glomus formosanum CNPAB020 can facilitate the translocation of Bradyrhizobium diazoefficiens USDA 110 in the rhizosphere ( de Novais et al, 2020 ) in addition to its main activity in nutrient transfer.…”
Section: Microbial Interactions Promote Rhizosphere Colonizationmentioning
confidence: 99%